Pelatihan Pembuatan Minuman Herbal Sebagai Upaya Peningkatan Imun Tubuh Pada Warga Desa Mencirim Kota Binjai - Sandy Yudha Sandy; Suci Ansaro; Dira Khairunisa (PUSLITABMAS-Politeknik Pariwisata Batamc, 2023)
The lack of public knowledge about medicinal plants and the properties of medicinal plants to increase body resistance or immunity. To overcome this problem, it is necessary to educate the public in the form of types of medicinal plants, their properties and how to use/process them appropriately based on an evidence-based scientific approach. The approach method used in community service activities is training in making herbal drinks for the community to increase the body's immunity with herbal drinks. The location of this extension activity was carried out in Mencirim Village, South Binjai District, Binjai City as a partner. During the one week training on making herbal drinks, the people of Mencirim Village were very enthusiastic and could even spend 40-50 bottles of herbal drinks every day.